Rational approximations to pie - Choong, K.Y.; Daykin, D.E.; Rathbone, C.R. (American Mathematical Society, 1971)
Using an IBM 1130 computer, we have generated the first 20, 000 partial quotients in the ordinary continued fraction representation of pie. © 1971 American Mathematical Society.